AN EVALUATION OF ADVERSE DRUG REACTIONS WITH REMDESIVIR IN PATIENTS OF COVID-19 - BASHINI, MIRUTHU; SHAH, SUCHI; DESAI, CHETNA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The aim of the study was to evaluate the adverse drug reactions (ADR) following Remdesivir therapy in patients of COVID-19. Methods: All patients more than 18 years of age of any gender, diagnosed with COVID-19 infection receiving remdesivir therapy and fulfilling the selection criteria were included in the study after informed consent. They were monitored for ADRs till end of treatment and analyzed for characteristics of the ADRs: Causality, severity, and preventability. Results: Out of 80 patients (mean age of 49.27±16.22 years) enrolled, 51 (63.75%) developed 84 ADRs. Most common ADRs included increased aspartate transaminases, (20.23%), increased bilirubin (19.04%), increased alanine transaminases (13.09%), increased creatinine (11.90%), and increased blood urea (9.52%). Causality assessment using WHO-UMC scale showed, 85.71% possible, 13.09% probable, and 1% certain causal association of the ADRs with remdesivir. A total 75% ADRs were mild in severity and 45% patients recovered from the event at the end of treatment. Conclusion: Hepatic and Renal dysfunctions are observed with remdesivir in COVID-19 patients. Intensive monitoring of ADRs with newer drugs with EUA such as remdesivir is warranted to ensure safer use in patients.